Deep impact - Leder, Mimi, 1952-; Freeman, Morgan; Leoni, Tea, 1966-; Duvall, Robert; Schell, Maximilian; Wood, Elijah, 1981-; Redgrave, Vanessa, 1937-; Cromwell, James; Horner, James; Paramount Pictures; Dreamworks Pictures ([United States] : Paramount, 2004)
'Deep Impact' is the story of the world's reaction to a death sentence. As a comet approaches the earth which might not be destroyed or diverted before it reaches earth, each individual struggles in the face of extinction to find what most matters to him or her.
Originally issued as a motion picture in 1998.
Special features: available commentary with director Mimi Leder and visual effects supervisor, Scott Farrar, preparing for the end, making an impact, creating the perfect traffic jam, parting thoughts, photo gallery, teaser trailer, theatrical trailers.
Morgan Freeman, Tea Leoni, Robert Duvall, Maximilian Schell, Elijah Wood, Vanessa Redgrave, James Cromwell.
DVD, NTSC, region 1, widescreen presentation; Dolby Digital.
Keywords: Comets -- Collisions with Earth; Feature films; Video recordings for the hearing impaired